Integrins as Therapeutic Targets for Respiratory Diseases - M. Teoh, C.; S.L. Tan, S.; Tran, T. (Current Molecular Medicine, 2015)
Integrins are a large family of transmembrane heterodimeric proteins that constitute the main receptors for extracellular matrix components. Integrins were initially thought to be primarily involved in the maintenance of cell adhesion and tissue integrity. However, it is now appreciated that integrins play important roles in many other biological processes such as cell survival, proliferation, differentiation, migration, cell shape and polarity. Lung cells express numerous combinations and permutations of integrin heterodimers. The complexity and diversity of different integrin heterodimers being implicated in different lung diseases present a major challenge for drug development. Here we provide a comprehensive overview of the current knowledge of integrins from studies in cell culture to integrin knockout mouse models and provide an update of results from clinical trials for which integrins are therapeutic targets with a focus on respiratory diseases (asthma, emphysema, pneumonia, lung cancer, pulmonary fibrosis and sarcoidosis).
Keywords: lung disease